Effect of sound therapy on whole scalp oscillatory brain activity and distress in chronic tinnitus patients - Jørgensen, Mie Lærkegård; Hyvärinen, Petteri; Caporali, Sueli; Dau, Torsten (Frontiers in Neuroscience, 2023)
Sound therapy is a common tinnitus treatment, where the tinnitus percept is either fully or partially masked by an external sound. Some tinnitus patients experience a decrease in tinnitus related distress after the use of sound therapy. Differences in the neural response to sound therapy may form a basis for classifying tinnitus patients. In this study, the long-term (2 months) effects of sound therapy on the oscillatory brain activity and tinnitus related distress were investigated in chronic tinnitus patients. Baseline oscillatory activity in the group of tinnitus participants was also compared to a matched control group. No differences were found in the oscillatory activity when comparing the tinnitus group to the control group. Differences were found for the frequency range between 27.5 Hz and 41.5 Hz corresponding to high beta and gamma power when comparing the tinnitus group before and after the use of sound therapy. Furthermore, a reduction of the tinnitus-related distress was found after the long-term use of sound therapy. However, there was no correlation between the changes in the oscillatory activity and the reductions of the tinnitus-related distress. Overall, the lack of correlation between the changes in tinnitus-related distress and changes in power activity hampers the interpretability of the findings and undermines the utility of using oscillatory activity as a biomarker for the effect of sound therapy treatment.